EGMR 37292/97 vom 28. Juni 2001 , CASE OF F.R. v. SWITZERLAND - Hudoc Ch (2001)
Violation of Art. 6-1;Pecuniary damage - claim dismissed;Non-pecuniary damage - finding of violation sufficient;Costs and expenses partial award; Violation: 6;6-1